Prototype Smart Security on Doors using RFID with Telegram Monitor NodeMCU Based - Mardianus; Andi Yusika Rangan; Salmon (Politeknik Pertanian Negeri Samarinda, 2021)
The application of prototype smart security tools on doors using RFID with a NodeMCU-based telegram monitor in the process of opening the door aims to provide security and comfort and make work easier to make it faster, more effective and efficient. Where it can be used by lecturers and assistant lecturers who have been registered as staff and admin of the Computer Laboratory and the results of the track record will be monitored by the Head of the STMIK Computer Laboratory, Widya Cipta Dharma. This prototype was built using the C programming language with the Arduino IDE (Integrated Development Environment) application, and the system in the form of WEB using the PHP Native programming language using the Sublime Text 3 application and using the Mysql database and using the Telegram application as a medium for receiving notifications in the form of messages to be received by head of the Computer Laboratory. Based on the data analysis carried out above, it is concluded that the application of Smart Security on doors using RFID with a NodeMCU-based Telegram monitor is much faster, effective, efficient and safe and easy to use.